Pengaruh Insentif Keuangan dan Kompleksitas Tugas terhadap Kinerja: Sebuah Studi Eksperimen - Clara Noviana Agustina Indriastuti; Adriana Marini Purwanto; Theodorus Radja Ludji (Jurnal Akuntansi, 2020)
This study used a 2x2 between-subject experiment to examine the relationship between monetary incentives, task complexity and performance. Monetary incentives in this study were applied in two types, piece-rate and fixed-rate, while task complexity was varied in two categories, low and high. Participants’ performance was measured through the completion of tasks assigned. Results of this study indicates no effect of monetary incentive on performance, yet there is a significant effect of task complexity on performance where participants provided with tasks with low complexity showed a significantly higher performance than participants provided with tasks with high complexity. Furthermore, this study finds no interaction between monetary incentives and task complexity on performance. It is implied from this study that monetary incentives were not the main factors that contribute towards employees’ performance in the companies. Besides, task complexity is an important factor to be considered by firms, as it can influence their employees’ performance. Keywords: Monetary Incentives, Task Complexity, Performance